IDENTIFIKASI ALIRAN AIR INJEKSI DI LAPANGAN TALANG JIMAR REGION SUMATRA MENGGUNAKAN METODE SPONTANEOUS POTENTIAL - Fithria I D, Ni'matul; Setyawan, Agus; Yulianto, Tony (BERKALA FISIKA, 2012)
Spontaneous-potential observation using amplitude potential method had been done beneathTalang Jimar area. The purpose of observation are to determine the distribution and depth of fluidinjection. Spontaneous-potential which has been corrected then processed using excel and surfer 9 toknow the distibution of its spread, while for the clarified of the deph we used spherical model. Thespontaneous-potential result shows ranging from -40 mV up to 10 mV with direction towards thereference block and a depth of 244,93 meters show.Keywords : Spontaneousâ€potential, fluid injection, Talang Jimar, spherical model.